Reconceptualising space in networked learning - Smith, Susan M. (Proceedings of the International Conference on Networked Learning, 2012)
This paper explores the learning processes within a higher education networked learning leadership programme made up of owner-managers of small to medium sized enterprises. Networked learning still has some way to go to fully realise its potential within and by the higher education sector. Accordingly, this paper seeks to contribute to our understanding of how to support networked learning communities and maximise their learning potential by focusing on learning spaces. Space has been a topic of discussion in much of the literature on learning and more often than not it focuses on the physical spaces and design for teaching and learning. This is particularly relevant for networked learning as our understanding about learning using technology is changing our ideas about learning spaces .This paper draws upon in depth qualitative research to conceptualise an alternative way of looking at learning spaces which calls for a different understanding of space within learning communities and networked learning. The central argument is that space in relation to learning can be reconceptualised through a different way of thinking about learning spaces. The four learning spaces proposed are; 1) peer-to-peer, 2) social, 3) reflective and 4) peripheral. It is argued these spaces act as a health check for networked learning communities as a way of looking at the taken for granted practices of the community. Consequently, they represent the social and cultural ways of being a member of a learning community. The learning spaces within this study are conceived of as both constructs and effects of the learning community’s engagement with networked learning. Used in this way they can be seen a viable way to rethink how facilitators in networked learning can support the learners. It is argued that they provide a compelling way of understanding the learning processes within networked learning and can be used as a litmus test to indicate whether a learning community is maximising its learning potential. Understanding the practices of this community can contribute to social theories of learning in order to develop our understanding of the complexities of learning within networked learning. Arguably the learning spaces themselves are a social theory of learning. The paper finishes by urging facilitators to nurture opportunities for the conceptual learning spaces with a set of recommendations in order to help the learning community maximise its learning potential.